Influence of the use of wastewater on nutrient absorption and production of lettuce grown in a hydroponic system - da Silva Cuba Carvalho, Renata [UNESP]; Bastos, Reinaldo Gaspar; Souza, Claudinei Fonseca (Elsevier, 2018)
The aim of this research was to evaluate the nutrient absorption and the fresh mass of lettuce plants cultivated using domestic wastewater in a hydroponic system during winter and summer seasons. The hydroponic system used was the Nutrient Film Technique with three treatments: 1) drinking water and chemical fertilizers (T1): 2) wastewater supplemented with chemical fertilizers (T2): and 3) only wastewater (T3) in a completely randomized experimental design with four replicates. The wastewater was previously characterized before being used in the treatments in order to quantify the need for nutrient supplementation in the T2 treatment. To determine the fresh mass, dry mass and nutrient absorption, three whole plant samples of each plot were collected at 1, 7, 14 and 21 days after transplanting. The nutrient absorption occurred according to a growing polynomial function for all treatments and most of the elements throughout the two cycles of the crop, except for potassium and magnesium in the T3 treatment in the winter crop. The results of fresh mass of the plant, pH and electrical conductivity of nutrient solutions were submitted to 2-way ANOVA, considering winter and summer as the first factor and treatments as the second one. A significant interaction between the factors for fresh mass and electrical conductivity was observed, and for that reason the average were submitted to Tukey test (p < 0.05%). For T1 and T2 treatments, significant differences were found between the average of the fresh mass of winter and summer, with higher values in winter. For the T3 treatment, no difference was found between the evaluated periods, but there was a significant difference in relation to the other treatments in both periods. The plants of this last treatment had lower fresh mass, less accumulation of nutrients and visual symptoms of nutritional deficiency. Under the experimental conditions, it was concluded that there was no difference in the nutrient absorption between the T1 and T2 treatment, but in the T3 treatment, the absorption was slower and smaller, demonstrating that it is necessary to supplement the wastewater with nutrients.
Keywords: Domestic effluent; Lactuca sativa L.; Mineral nutrition